Pengaruh Relationship Marketing Terhadap Customer Satisfaction Pada PT Pegadaian Cabang Syariah Pekanbaru - Dewi, Diana Sri; Febrina, Dian (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
This Research Aims To Examine The Influence Of Relationship Marketing On Customer Satisfaction. Therefore The Variables Used Are Trust, Reciprocity, Commitment And Communication. The Type Of The Research Is Explanatory Research With Quantitative Approach. In This Study, Data Was Collected Through Questionnaires From 114 Customers. Quantitative Analysis Includes Verification, Reliability Testing, And Normality Testing. Data Analysis Technique Using A Simple Linear Test, Which Is Used To Test Hypothesis Using T-Test And Deterministic Test. From The Results Of Data Processing Via Spss, The Number Of T Is 3,304 , And From The Percent Distribution Of T, The Table T Is 1, 1981 . While The Table T Count > T, And The Significance Level Is Also 0.001 And Lt; 0.05. Therefore, The Results Of Hypothesis Testing In This Study Indicate That The Relationship Marketing Has An Influence On The Customer Satisfaction In Pegadaian Syariah Pekanbaru.Â The Relationship Between Relationship Marketing Variable (X) And Customer Satisfaction (Y) Is Positive, As Evidenced By A Regression Coefficient Of Y= 4,658+0,230X , Which Means That Every 1% Increase In The Monitored Variable Will Increase Customer Satisfaction By 4,658. The Value Of The Coefficient Of Determination (R Squared) Is 0,583 Relationship MarketingÂ Had A 58,30 % Influence On Customer Satisfaction In Pegadaian Syariah Pekanbaru